Prevalence of non-communicable diseases and their risk factors in Papua New Guinea: A systematic review. (November 2020) - Rarau, Patricia; Guo, Shuaijun; Baptista, Shaira Nicole; Pulford, Justin; McPake, Barbara; Oldenburg, Brian
Introduction: The mortality associated with non-communicable diseases has increased significantly in most countries in the World Health Organization Western Pacific Region over the last 20 years, as have the underlying risk factors. This study aimed to collate evidence on the prevalence of four major non-communicable diseases and their risk factors in Papua New Guinea in order to inform appropriate policy for their prevention and management. Methods: We performed a systematic review of Papua New Guinea-based population prevalence studies of cardiovascular diseases, type 2 diabetes mellitus, chronic respiratory diseases, and cancers, as well as non-communicable disease risk factors published before 2016. Five online databases were searched and screened against eligibility criteria according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: A total of 57 articles were included in this review, most of which (n = 48) were published prior to 2000. Eleven articles reported on diabetes, six reported on chronic lung disease/asthma, two reported on cardiovascular diseases, and two reported cancer as the primary outcome, while the remaining 36 papers reported non-communicable disease risk factors. Conclusion: This review demonstrated variations in the prevalence of non-communicable diseases (0%–19%) and their risk factors (0%–80.6%) attributed to the lifestyle and genetic diversity of the Papua New Guinea population. There is a strong suggestion that the prevalence of non-communicable diseases (particularly type 2 diabetes mellitus) and key non-communicable disease risk factors (hypertension, overweight, and obesity) has increased, but there is a lack of recent data. As such, there is an urgent need for new and up-to-date data in all areas of Papua New Guinea.